Peran Disiplin Kerja, Kompetensi dan Komunikasi Terhadap Kinerja Pegawai Melalui Motivasi Kerja (Studi Pada Kecamatan Sukoharjo) - Sulistyani, Lilis; Pristiani, Andria (BISMA : Business and Management Journal, 2023)
The aim of the research is to know, test and analyze the role of work discipline, competence and communication on work motivation and employee performance in Sukoharjo District. Collection technique with the questionnaire method. The sample with census technique is 50 respondents. Data analysis includes instrument testing, linearity testing, hypothesis testing, and path analysis. The results of the study prove that competence has a significant effect on work motivation, but work discipline and communication have no significant effect; work discipline, communication and work motivation have a significant effect on performance but competence has no significant effect. The results of the F test prove that work discipline, competence, communication and work motivation have a significant effect on performance. Results The total R2 value of 0.972 means that employee performance is explained by work discipline, competence, communication and work motivation of 97.2% and the remaining 2.8% is explained by other variables outside the model. The results of path analysis show that the direct path of work discipline is the dominant and significant path in improving performance. The use of intervening variables Work motivation is effective in mediating competency on performance. However, it is not effective in mediating work discipline and communication on performance